Women Professors Who Makes It and How? - Diezmann, Carmel; Grieshaber, Susan; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2019)
This book explores the career paths of Australian women who have succeeded in achieving professorships and beyond, where for the most part, such positions are predominately occupied by males. It also explores the gendered culture that exists across faculties and universities as reported by participants in a survey questionnaire of 525 new professors (female and male), and nearly 30 interviews of women in Australian higher education, either in small focus groups or individually. Futher, it identifies catalysts for and inhibitors of success for women and looks in depth at (3z(Bthe boys$1 (Bclub(3y (Band how it impacts women$1 (Bs progression. The book also highlights how critical life decisions $1 (Bdoctoral study, work and family $1 (Bshape the careers of academic women. It identifies five distinct career profiles for women academics and the pressure points and effective support for each profile. Thus, this book can assist women academics who are making life decisions and those supporting their career progression. It also provides insights into why affirmative action initiatives to improve the proportion of women in the professoriate have had minimal impact despite considerable investment over the past 30 years. .s
1 Women in the Professoriate -- 2 The Higher the Fewer -- 3 Climbing the Ladder -- 4 Research Context and Design -- 5 Research Kaleidoscope -- 6 Snakes and Ladders -- 7 The Boy' Club -- 8 Luck, the Double Edged Sword -- 9 Critical Events and Academic Women's Career Profiles -- 10 Navigating Rush Hours.
Keywords: Higher education; Educational sociology; Sociology; Higher Education; Sociology of Education; Gender Studies